Proximal Femoral Locking Plate (PFLP ) A Salvage Option in Nonunion of Proximal Femoral Fractures - Hari Om Aggarwal; Singh M; Sareen S (GMC Patiala Journal of Research and Medical Education, 2018)
Nonunion of intertrochanteric fractures is uncommon because there is excellent blood supply and good cancellous bone in the intertrochanteric region of the femur. When primary fixation of proximal femoral fractures with implants fails, revision osteosynthesis may be challenging. Tracts of previous implants and remaining insufficient bone stock in the proximal femur pose unique problems for the treatment. Intramedullary implants like proximal femoral nail (PFN) or surface implants like Dynamic Condylar Screw (DCS) are few of the described implants for revision surgery. There is no evidence in the literature to choose one implant over the other. We used the proximal femoral locking compression plate (PFLP) in one case undergoing revision surgery. We aimed to evaluate the efficacy of this implant in salvage situations. Patient with primary proximal femoral fracture (reverse oblique type) was treated with DHS and plate and subsequently went into non union because of implant failure. Fracture united satisfactorily after fixation with PFLP and bone grafting, without any complications.